Pengaruh Kegiatan Shalat Dhuha Terhadap Pembentukan Karakter Disiplin Siswa Kelas XI Di Madrasah Aliyah Al Musaddadiyah Garut - Sulaiman, Husnan; Mastoah, Mimi (STAI Al-Musaddadiyah Garut, 2023)
The current wave of globalization has made it challenging for children to engage in religious practices, respect others, and resist the influence of external cultures, leading to significant issues regarding students' character. Character education serves as a fundamental cornerstone for a nation and must be instilled in children from an early age. In reality, schools face various moral deviations among students, such as a lack of discipline and responsibility. Examples include not participating in Dhuha prayer as per school regulations, arriving late, not wearing the school uniform, failing to do homework, disobeying school rules, defacing desks, dressing untidily, submitting assignments late, disturbing classmates during lessons, and frequent fighting among peers. In response, one approach implemented is the development of student discipline through Dhuha prayer activities. Teachers conceptualize these activities to enhance students' personalities and improve their discipline. The objectives of this research are: 1) To describe the implementation of Dhuha prayer activities at MA Al-Musaddadiyah Garut, 2) To detail the discipline character of 11th-grade students at MA Al-Musaddadiyah Garut, and 3) To examine the influence of Dhuha prayer activities on developing disciplined character in 11th-grade students at MA Al-Musaddadiyah Garut. This study employs an inferential quantitative method to explore the relationship between the independent variable (Dhuha prayer) and the dependent variable (student discipline character). The subjects of this study are 34 students from the 11th grade at MA Al-Musaddadiyah Garut. The findings reveal that the influence of Dhuha prayer activities scores an average of 4.37, falling within the 4.01-5.00 interval, categorized as